The Fourier transforms of Lipschitz functions on certain domains - M. S. Younis (International Journal of Mathematics and Mathematical Sciences)
The Fourier transforms of certain Lipschitz functions are discussed and compared with the Hankel transforms of these functions and with their Fourier transforms on the Euclidean Cartan Motion group M(n), n≥2.